Exploring community institutions as instruments for strengthening tree-based livelihoods in Nyando - Misiko, Michael T. (2012)
The objective of this study was to analyse suitability of community institutions as stakeholders in a C finance initiative in Nyando, Kenya. This work purposively sampled registered groups with sound organisation, and not the numerous small informal entities in Nyando. Studied institutions were by and large livelihood entities. They were selected because they engaged in generation and sharing of collective benefits. This aspect of benefits sharing is critical, because such groups are considered as possible conduits for equitable disbursement or even management of revenues that may be generated in the future from C finance initiatives.